Intervensi Keperawatan “Ekofol” pada Pasien Post PCI dalam Meningkatkan Kepatuhan Pengobatan - Pebrianti, Sandra; Shalahuddin, Iwan; Eriyani, Theresia; Nugraha, Bambang Aditya (Universitas Malahayati, 2024)
ABSTRACT Percutaneous coronary intervention (PCI) is the most common therapy for treating CAD through improved myocardial perfusion. The transition from hospital to home is a challenge for CAD patients undergoing PCI. After a brief stay in the hospital, patients have to take a lot of medicine every day, and adjust their lifestyle at home. The purpose of conducting this Evidence Based Practice is to determine the types of nursing interventions that can improve the level of treatment adherence in post PCI patients. The research method used in this review literature is a narrative review type with the title